Effects of a Mix of Carbohydrases on Live Performance and Carcass Yield of Broilers Fed All Vegetable Diets Based on Corn and Soybean Meal - Vieira, S.L.; Ott, R.P.; Berres, J.; Olmos, A.R.; Coneglian, J.L.B.; Freitas, D.M. (International Journal of Poultry Science, 2006)
A study was conducted to compare live performance and the yield of carcass and commercial cuts of broiler chickens fed all vegetable diets supplemented with a mix of enzymes targeting the carbohydrate fraction of soybean meal. All vegetable diets, antibiotic free, were formulated with corn and soybean meal as major ingredients. Treatments were a dietary Control without enzymes and diets composed by the supplementation to produce the other treatments with a xylanase (EC 3.2.1.8), a pectinase (EC 3.2.1.15) and a alpha-galactosidase (EC 3.2.1.22) in the amount of 100 grams per Ton each. These enzymes were included in the feeds over the top at the expense of corn individually, on a two by two basis, or the three altogether, in a total of 8 treatments. Two thousand eight hundred and eighty one-d-old Ross X Ross 308 male broiler chicks were placed in 2.30 X 1.75 m floor pens, 40 birds in each, 7 replicates per treatment. Results demonstrated an overall absence of response for enzyme inclusion in live performance, carcass and cuts. However, data evaluated on a weekly basis demonstrated significative differences in the period of 28 to 37 d of age for the Xylanase inclusion. No response in the most of bird responses for the three enzymes added in combination may be related to inefficacy of the enzymes in the doses included. Other interferences; however, cannot be discharged.